Cardiac magnetic resonance imaging in assessing heart function in patients with Ebstein's anomaly. (14th October 2021) - Mochula, O; Troshkinev, N; Krivoshchekov, E; Ussov, W
Abstract:  : Ebstein's anomaly (AE) is a rare congenital heart disease in which the development of the tricuspid valve (TV) and right ventricular myocardium (RV) is impaired. Evaluation of the RV using echocardiography has certain difficulties due to the irregular shape, these limitations can be overcome by CMR. CMR helps the surgeon to assess the degree of tissue delamination of all leaflets from the RV, to determine the boundaries of the atrialized part of the RV, as well as to assess the effectiveness of the operation. Purpose: To assess changes in the areas of the heart chambers in patients with Ebstein's anomaly and in the long-term period after cone reconstruction using magnetic resonance imaging. Methods: Conducted a single-center, retrospective study. The study included 9 patients with AE and 15 patients in the long-term period after cone reconstruction. The average age was 6.08 [2; 10] years, weight - 26.73 [12.5; 33] kg, height 116.24 [90; 137] cm, body surface area 0.9 [0.55; 1.06] m 2 . CMR was performed before operation and upon admission for a follow-up examination in the long-term period. CMR was performed on tomography with a magnetic field induction of 1.5 T. To visualize the TV, dynamic images were used in 2- and 4-chamber projection. We used the method of assessing the area of each heart chamber separately in systole and diastole according to the CMR. Results: According to the CMR, there were changes in the area before operation in each chamber in systole and diastole, except for the atrialized part of the RV. There were statistically significant changes in the functional part of the RV before operation in a 4-chamber projection in systole 5.73 [4.15; 8.2] mm 2 and diastole 11.76 [7.35; 17.2] mm 2 and in a 2-chamber position in systole 34.3 [23.25; 44.65] mm 2 and diastole 45.66 [33.85; 54.4] mm 2 (p=0.001 and p=0.025, respectively). The areas of the RA, LA, LV also had statistically significant changes in systole and diastole. Statistical analysis showed significant results in all parts of the heart, except for the atrialized part of the RV before operation (p=0.4 and p=0.092) in 2-, 4-chamber projections. Comparison of chambers before and after operation in % ratio showed that the area of the functional part of the RV increased after cone reconstruction, due to the exclusion of the atrialized part and suturing of the edge of the TV leaflets to the true annulus fibrosus. Conclusion: The use of CMR, in patients with Ebstein's anomaly before operation and in the long-term period, to assess the areas of the heart chambers, confirmed the absence of contractility in the atrialized part of the RV and the need for its suturing. Moving the point of closure of the TV leaflets to the true annulus fibrosus and excluding the atrialized part during conical reconstruction allows increasing the area of the functional part of the RV with a positive effect on the hemodynamics of the heart. Funding Acknowledgement: Type of funding sources: None.